Affairs of honor : national politics in the New Republic - Freeman, Joanne B., 1962- (New Haven : Yale University Press, 2001)
"In this book, Joanne Freeman offers a major reassessment of political culture in the early years of the American republic. By exploring both the public actions and private papers of key figures like Thomas Jefferson, Aaron Burr, and Alexander Hamilton, as well as less famous politicians such as Senators William Maclay and William Plumer, Freeman reveals an alien and profoundly unstable political world grounded on the code of honor. In the absence of a party system and with few examples to guide America's great experiment in republican governance, national politicians monitored their conduct and attacked their rivals according to the ethic of honor."
Contents -- Acknowledgments -- Introduction -- Prologue: Walking on Untrodden Ground: The Challenges of National Politics -- 1. The Theater of National Politics -- 2. Slander, Poison, Whispers, and Fame: The Art of Political Gossip -- 3. The Art of Paper War -- 4. Dueling as Politics -- 5. An Honor Dispute of Grand Proportions: The Presidential Election of 1800 -- Epilogue: Constructing American History -- A Note on Method -- Notes -- Bibliography -- Index
Includes bibliographical references (pages 347-364) and index.
Print version record.
JSTOR
Keywords: Political culture -- United States -- History -- 18th century; Politics and culture -- United States -- History -- 18th century; Elite (Social sciences) -- Political activity -- United States -- History -- 18th century; Honor -- Political aspects -- United States -- History -- 18th century; United States -- Politics and government -- 1789-1815.; United States -- Social conditions -- To 1865.; Politique et culture -- États-Unis -- Histoire -- 18e siècle.; Élite (Sciences sociales) -- Activité politique -- États-Unis -- Histoire -- 18e siècle.; Honneur -- Aspect politique -- États-Unis -- Histoire -- 18e siècle.; États-Unis -- Politique et gouvernement -- 1789-1815.; États-Unis -- Conditions sociales -- Jusqu'à 1865.; HISTORY -- General; Elite (Social sciences) -- Political activity; Honor -- Political aspects; Political culture; Politics and culture; Politics and government; Social conditions; United States; Politische Kultur; Elite; Politisches Engagement; USA; Politieke cultuur; Elites; Eer; To 1865; History